Penerapan Kaidah Fiqih Jinayah dalam Qadzaf Secara Kinayah - Hafid Gunawan; Nina Nirmala Sari; Muhammad Akmal Muzhafar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the application of Islamic criminal law (fiqih jinayah) principles, specifically in the case of qadzaf—accusation of adultery without valid proof—when conveyed through kinayah (indirect or allusive expressions). The focus is on how legal maxims such as al-ḥudūd tudra’ bi al-syubuhāt and al-aṣl barā’at al-dzimmah are employed to assess the legal validity of ambiguous accusations. This research adopts a qualitative approach through library research, analyzing both classical and contemporary Islamic legal texts. The findings reveal that qadzaf in the form of kinayah does not meet the criteria for ḥadd punishment due to its interpretive uncertainty and lack of clear evidence. Therefore, ta'zir—a discretionary punishment—should be applied instead, based on public interest and judicial discretion. This study is significant in addressing modern social communication dynamics, especially in the digital age, and contributes to a fair, contextual, and cautious implementation of Islamic criminal law.